Analysis of Factors Associated with Contact Dermatitis in PT. Cosmas Indonesia - Suryani, Febria; Iting Shofwati (Scientific Journal of Dermatology and Venereology, 2023)
Introduction: Contact dermatitis is a skin disorder that is quite common, especially due to exposure to certain materials or substances due to work. PT. Cosmas Indonesia is a cosmetics manufacturing company that processes and produces various cosmetics. In the process of making these cosmetics, this company very often uses various chemicals, both in the form of strong bases and various organic solvents. Of course, this company is very susceptible to skin disorders in its workers. This study aimed to analyze the factors associated with contact dermatitis in PT. Cosmas Indonesia. Methods: Cross-sectional analytic observational study. A total of 50 research subjects participated in this study. Observation risk factor and sociodemographic data were carried out in this study. Data analysis was carried out using SPSS using univariate and bivariate. Results: The incidence of contact dermatitis occurs in workers with a longer working period than in workers who do not experience contact dermatitis. Personal hygiene that is not good is also a problem factor risks associated with contact dermatitis. Conclusion: The length of time exposure to chemical compounds and personal hygiene becomes an important factor role in the incidence of contact dermatitis in the study of PT. Cosmas Indonesia.